1994
DOI: 10.1200/jco.1994.12.7.1394
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy for invasive bladder cancer: prognostic factors for survival of patients treated with M-VAC with 5-year follow-up.

Abstract: The stage of bladder cancer at presentation and at postchemotherapy pathologic staging are independent prognostic factors for long-term survival in patients treated with neoadjuvant chemotherapy. Downstaging after neoadjuvant chemotherapy was associated with improved survival in patients with muscle-invasive bladder cancers, but only for those with extravesical disease (T > or = 3B) pretreatment. Randomized comparisons will be required to assess the impact of chemotherapy on overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(46 citation statements)
references
References 0 publications
3
43
0
Order By: Relevance
“…11 Tumor stage at diagnosis is an independent predictor of bladder cancer survival. 12,13 Although a stage disparity persists between blacks and other ethnic groups, the gap has narrowed somewhat over the last 30 years. Black patients today are more likely to present with localized disease than their historical counterparts.…”
Section: Commentmentioning
confidence: 99%
“…11 Tumor stage at diagnosis is an independent predictor of bladder cancer survival. 12,13 Although a stage disparity persists between blacks and other ethnic groups, the gap has narrowed somewhat over the last 30 years. Black patients today are more likely to present with localized disease than their historical counterparts.…”
Section: Commentmentioning
confidence: 99%
“…Initial tumor stage and clinical response to chemotherapy were found to be independent prognostic factors. In multivariate analysis, attainment of PO status was the only significant prognostic factor for survival (34). These data demonstrate that response to chemotherapy is a prognostic factor of extreme importance, and should be considered when making clinical decisions for our patients.…”
Section: Neo-adjuvant Chemotherapymentioning
confidence: 83%
“…Since there are no tumor markers yet that can beforehand detect responders to NAC, certain clinicopathological factors were suggested to affect the treatment response. The relation between the response rate and stage of the 1 ry tumor was previously proved in a trial done by Schultz et al who reported overall response rates after neoadjuvant MVAC in patients with T3b and T4a tumors to be approximately 81% and 9%, respectively 23 . In the present study the overall response rate in patients with T3 was 88% and in patients with T4 was 57% (p = 0.02).…”
Section: Discussionmentioning
confidence: 99%